Exploring Changes in Teachers' Views on Assessment Practices at Madrasah Ibtidaiyah - Adji, Waluyo Satrio; Nadir, Muhammad; Damayanti, Ibanez Sheila Anggi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study investigates alterations in educators' perspectives at Madrasah Ibtidaiyah Batu Town regarding the use of formative and summative evaluations in education following their participation in training. The study employs a research-oriented community service methodology utilizing the Asset-Based Community Development (ABCD) paradigm to optimize the inherent strengths and resources within the teaching community. Data was collected through pre-tests and post-tests completed by teachers regarding their understanding of the role of assessment in providing feedback, modifying learning plans, and monitoring student progress. The results of this study indicate that training with the ABCD method successfully changed the conceptual understanding of Batu City Elementary School teachers regarding pedagogical assessment (formative and summative) while strengthening the evidence that top-down training is effective in changing educators' perspectives on evaluation.